1987
DOI: 10.1017/s0003356100012368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ambient temperature on energy metabolism in growing pigs

Abstract: Group-housed young growing pigs, given food ad libitum, were exposed to two temperatures, one within thermal neutrality (25°C) and one around the lower critical temperature (15°C). Pigs at 15°C had daily gains reduced by 57 g for 6 days after initial exposure. Food intake was increased significantly after 6 days at 15°C but not at 25°C. Maintenance requirement was increased by 58 kJ/kg M" 75 and energy retained as protein was decreased by 49 kJ/kg M°7 5 for the first 6 days after exposure to the treatment of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Early weaned pigs (R 2 = 0.062; P = 0.125): Cairnie and Pullar, 1957Ota et al, 1975LeDividich et al, 1980Harmon et al, 1997McCracken and Gray, 1984 Body Mass (kg) Heat Production (W/kg) Bond et al, 1959Close and Mount, 1978Noblet and LeDividich, 1982McCracken and Gray, 1984van der Hel et al, 1984George, 1987Nienaber et al, 1987Verhagen et al, 1988Henken et al, 1993Brown-Brandl et al, 1998Brown-Brandl et al, 2001aBrown-Brandl et al, 2001bCollin et al,2001Quiniou et al, 2001 Brown-Brandl, 2002 Grow-finish pigs (R 2 = 0.835; P < 0.0001): HP (W/kg) = (14.95 ±1.08)m (-0.40 ±0.02)…”
Section: Heat Production Data In Thermoneutral Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early weaned pigs (R 2 = 0.062; P = 0.125): Cairnie and Pullar, 1957Ota et al, 1975LeDividich et al, 1980Harmon et al, 1997McCracken and Gray, 1984 Body Mass (kg) Heat Production (W/kg) Bond et al, 1959Close and Mount, 1978Noblet and LeDividich, 1982McCracken and Gray, 1984van der Hel et al, 1984George, 1987Nienaber et al, 1987Verhagen et al, 1988Henken et al, 1993Brown-Brandl et al, 1998Brown-Brandl et al, 2001aBrown-Brandl et al, 2001bCollin et al,2001Quiniou et al, 2001 Brown-Brandl, 2002 Grow-finish pigs (R 2 = 0.835; P < 0.0001): HP (W/kg) = (14.95 ±1.08)m (-0.40 ±0.02)…”
Section: Heat Production Data In Thermoneutral Conditionsmentioning
confidence: 99%
“…Second, there were no studies reported between 1988 and 1993. Third, it was decided the data reported by Nienaber et al (1987) was obtained using moderate growth genetics, but the data reported by Verhagen et al (1988) used a high-lean genetic line with similar performance to the more recent data. Figures 5 and 6 show the data trendlines of the two categories and compare the data to the CIGR Handbook (CIGR, 1999).…”
Section: Heat Production Data In Thermoneutral Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolizability of feed was measured for successive periods of 6 days, in order to assess partitioning of energy into energy requirement for maintenance and for ac cretion of protein and fat, as reported elsewhere (Verhagen et al, 1987). Intake of metabolizable energy (calculated from gross energy in feed minus ener gy in faeces, urine and refused feed) was expressed with reference to metabolic body size (metabolizable energy divided by body mass to the power 0.75 (m 0 75 ex pressed in kg 0,73 ) and by time).…”
Section: Measurementsmentioning
confidence: 99%